Adhesive agent composition, adhesive agent film for circuit connection, circuit connection structure, and method for manufacturing the same
Patent Information
- Application Number
- JP2023134528
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-22
- Publication Date
- 2025-03-07
AI Technical Summary
【0012】 本発明によれば、低温短時間接続(低温短時間硬化)が可能なラジカル硬化系接着剤であって、仮固定力にも優れる回路接続用接着剤フィルム及びそのような接着剤フィルムを形成することができる接着剤組成物、並びに、回路接続構造体の製造方法及び回路接続構造体を提供することができる。
Smart Images

Figure 2025029739000003 
Figure 2025029739000004 
Figure 2025029739000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive composition, an adhesive film for circuit connection, a circuit connection structure, and a method for producing the same. [Background technology]
[0002] Conventionally, various adhesive materials have been used to connect circuits. For example, an adhesive film for circuit connection having anisotropic conductivity in which conductive particles are dispersed in the adhesive is used as an adhesive material for connecting a liquid crystal display and a tape carrier package (TCP), connecting a flexible printed circuit board (FPC) and a TCP, or connecting an FPC and a printed wiring board.
[0003] In recent years, with the high integration of semiconductor elements and the high definition of liquid crystal display elements, the pitch between elements and between wirings has become narrower, and the heat generated during curing may adversely affect peripheral components. Furthermore, in order to reduce costs, it is necessary to improve throughput, and adhesion at low temperatures (90 to 170°C) and in a short time (within 1 hour, preferably within 10 seconds, more preferably within 5 seconds), in other words, adhesion at low temperatures and short curing times (low temperature and fast curing), is required. In order to achieve this low temperature and short curing time, it is necessary to use a thermal latent catalyst with low activation energy, but it is known that it is very difficult to provide storage stability at around room temperature.
[0004] For this reason, radical curing adhesives that use a (meth)acrylate derivative in combination with a peroxide as a radical polymerization initiator have been attracting attention. The radical curing system is a curing system that can be cured in a short time because the radicals, which are reactive species, are highly reactive, and the peroxide exists stably below the decomposition temperature of the radical polymerization initiator, so that it is a curing system that can be cured in a short time at low temperature and has both storage stability (for example, storage stability around room temperature). For example, radical curing adhesive compositions such as those shown in the following Patent Documents 1 to 3 are known. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2006-22231 A [Patent Document 2] JP 2009-1765 A [Patent Document 3] International Publication No. 2009 / 063827 Brochure Summary of the Invention [Problem to be solved by the invention]
[0006] When circuit members are connected to each other using an adhesive film for circuit connection, the adhesive film is usually laminated to one circuit member, and then the other circuit member is aligned so that the circuit electrodes of both members face each other, and then heated and pressed to temporarily fix the circuit members to each other. The temporarily fixed circuit members are transported to a device that performs a pressure bonding process, and a permanent connection is performed in which the opposing circuit electrodes are electrically connected to each other by thermocompression bonding.
[0007] Before being fully connected, the circuit components are temporarily fixed to each other by the adhesive strength of the adhesive film. If the fixing strength is insufficient, the circuit components are likely to become misaligned or fall off during transportation.
[0008] Recently, the connecting portions of semiconductor elements and liquid crystal display elements have become smaller and smaller, and adhesive films for circuit connection are required to be able to sufficiently temporarily fix circuit members together even with a smaller connecting area.
[0009] Therefore, the present invention aims to provide an adhesive film for circuit connection that is a radical-curing adhesive capable of low-temperature, short-time connection (low-temperature, short-time curing) and also has excellent temporary fixing strength, an adhesive composition that can form such an adhesive film, and a method for producing a circuit connection structure and a circuit connection structure. [Means for solving the problem]
[0010] The gist of the present invention is the following [1] to [8].
[0011] [1] An adhesive composition comprising a thermoplastic resin, a radical polymerizable compound, and a radical polymerization initiator, wherein the radical polymerizable compound comprises a first (poly)urethane (meth)acrylate compound having a weight average molecular weight of 10,000 to 55,000, and a second (poly)urethane (meth)acrylate compound having a weight average molecular weight of 500 to 1,500. [2] The adhesive composition according to [1], wherein the second (poly)urethane (meth)acrylate compound has an allophanate bond in the molecule. [3] The adhesive composition according to [1] or [2], wherein the content of the second (poly)urethane (meth)acrylate compound is 5 to 35 parts by mass per 100 parts by mass of the first (poly)urethane (meth)acrylate compound. [4] An adhesive film for circuit connection comprising a thermoplastic resin, a radical polymerizable compound, and a radical polymerization initiator, wherein the radical polymerizable compound contains a first (poly)urethane (meth)acrylate compound having a weight average molecular weight of 10,000 to 55,000, and a second (poly)urethane (meth)acrylate compound having a weight average molecular weight of 500 to 1,500. [5] The adhesive film for circuit connection according to [4], wherein the second (poly)urethane (meth)acrylate compound has an allophanate bond in the molecule. [6] The adhesive film for circuit connection described in [4] or [5], wherein the content of the second (poly)urethane (meth)acrylate compound is 5 to 35 parts by mass per 100 parts by mass of the first (poly)urethane (meth)acrylate compound. [7] A circuit connection structure comprising: a first circuit member having a first electrode; a second circuit member having a second electrode; and a connection portion disposed between the first circuit member and the second circuit member and electrically connecting the first electrode and the second electrode to each other, wherein the connection portion comprises a cured product of the adhesive composition according to any one of [1] to [3]. [8] A method for producing a circuit connection structure, comprising a step of thermocompression bonding a first circuit member having a first electrode and a second circuit member having a second electrode, with an adhesive film for circuit connection described in any one of [4] to [6] interposed between the first circuit member and the second circuit member, to electrically connect the first electrode and the second electrode to each other. Effect of the Invention
[0012] According to the present invention, it is possible to provide an adhesive film for circuit connection that is a radical curing adhesive capable of low-temperature short-time connection (low-temperature short-time curing) and also has excellent temporary fixing strength, an adhesive composition capable of forming such an adhesive film, as well as a method for producing a circuit connection structure and a circuit connection structure.
[0013] According to the adhesive film for circuit connection of the present invention, sufficient temporary fixing force can be obtained even when the connection area between circuit components is smaller, and the occurrence of the above-mentioned problems during transportation of the temporarily fixed circuit components can be suppressed. [Brief description of the drawings]
[0014] [Figure 1] 1 is a schematic cross-sectional view showing one embodiment of a connection structure according to the present invention. [Diagram 2] 2A to 2C are schematic cross-sectional views showing a manufacturing process of the connection structure shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] In this specification, the numerical range indicated by "~" indicates a range including the numerical values described before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a certain stage of the numerical range may be replaced with the upper limit or lower limit of the numerical range of another stage. In the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in the examples. In addition, the upper limit and lower limit values described individually can be arbitrarily combined. In this specification, "(meth)acrylate" means at least one of acrylate and the corresponding methacrylate. The same applies to other similar expressions such as "(meth)acryloyl". In addition, "(poly)" means both the case with and without the prefix "poly". In addition, "A or B" may include either A or B, or may include both. In addition, the materials exemplified below may be used alone or in combination of two or more types, unless otherwise specified. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified.
[0016] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the drawings where necessary. However, the present disclosure is not limited to the following embodiments.
[0017] <Adhesive composition> The adhesive composition of the present embodiment contains (A) a thermoplastic resin (hereinafter also referred to as "component (A)"), (B) a radically polymerizable compound (hereinafter also referred to as "component (B)"), and (C) a radical polymerization initiator (hereinafter also referred to as "component (C)"), and contains, as component (B), a first (poly)urethane (meth)acrylate compound (hereinafter also referred to as "component (B1)") having a weight average molecular weight of 10,000 to 55,000, and a second (poly)urethane (meth)acrylate compound (hereinafter also referred to as "component (B2)") having a weight average molecular weight of 500 to 1,500.
[0018] In this specification, the weight average molecular weight refers to a value measured by gel permeation chromatography (GPC) and converted using a calibration curve based on standard polystyrene.
[0019] [Component (A): Thermoplastic resin] Examples of the thermoplastic resin include polyurethane resin, polyimide resin, polyamide resin, phenoxy resin, poly(meth)acrylic resin, polyester resin, and polyvinyl butyral resin. These may be used alone or in combination of two or more.
[0020] The weight average molecular weight of the thermoplastic resin may be 5000 to 400000, 5000 to 200000, or 10000 to 150000. When the weight average molecular weight of the thermoplastic resin is 5000 or more, the adhesive strength of the adhesive composition tends to be good, and when the weight average molecular weight is 400000 or less, the compatibility with other components tends to be good, and a decrease in the fluidity of the adhesive tends to be suppressed.
[0021] As the thermoplastic resin, a rubber component may be used for the purpose of stress relaxation and improving adhesion. Examples of the rubber component include natural rubber, acrylic rubber, polyisoprene, polybutadiene, butyl rubber, carboxyl-terminated polybutadiene, hydroxyl-terminated polybutadiene, 1,2-polybutadiene, carboxyl-terminated 1,2-polybutadiene, hydroxyl-terminated 1,2-polybutadiene, styrene-butadiene rubber, hydroxyl-terminated styrene-butadiene rubber, acrylonitrile-butadiene rubber, nitrile rubber, carboxylated nitrile rubber, hydroxyl-terminated poly(oxypropylene), alkoxysilyl-terminated poly(oxypropylene), poly(oxytetramethylene) glycol, polyolefin glycol, and poly-ε-caprolactone. From the viewpoint of improving adhesion, the rubber component may have a highly polar group, a cyano group or a carboxyl group, as a side chain group or a terminal group. These rubber components may be used alone or in combination of two or more.
[0022] From the viewpoint of achieving both adhesive strength, film formability, and flowability, the content of component (A) in the adhesive composition may be 20 to 90 mass %, 20 to 80 mass %, or 30 to 70 mass % based on the resin components of the adhesive composition (e.g., components other than the conductive particles and filler).
[0023] [Component (B): radically polymerizable compound] As the (B) component, a compound having a radically polymerizable functional group can be used. Examples of the radically polymerizable functional group include a vinyl group, an acryloyl group, and a methacryloyl group. Of these, a compound having an acryloyl group and / or a methacryloyl group may be used. As the (B) component, one type can be used alone, or two or more types can be used in combination.
[0024] The adhesive composition of the present embodiment contains, as component (B), a first (poly)urethane (meth)acrylate compound (B1) having a weight average molecular weight of 10,000 to 55,000, and a second (poly)urethane (meth)acrylate compound (hereinafter also referred to as "component (B2)") having a weight average molecular weight of 500 to 1,500.
[0025] Examples of the (poly)urethane (meth)acrylate compound include compounds in which a (meth)acryloyl group is introduced into the terminal or side chain of a polyurethane resin. The polyurethane resin can be obtained by reacting a polyol with an isocyanate such as a diisocyanate, and the (meth)acryloyl group can be introduced by using a (meth)acrylate compound having a hydroxyl group such as 2-hydroxyethyl acrylate or 2-hydroxybutyl acrylate.
[0026] From the viewpoint of achieving both suppression of shrinkage after connection and ensuring adhesive strength when connecting circuit components, the (B1) component may be a (poly)urethane (meth)acrylate compound having a carbonate skeleton, or a compound in which a (meth)acryloyl group has been introduced into a polyurethane resin obtained by reacting a polycarbonate polyol with an alicyclic diisocyanate.
[0027] The component (B1) may be bifunctional.
[0028] The weight average molecular weight of the component (B1) may be from 10,000 to 55,000, or from 10,000 to 25,000, from the viewpoint of making it easier to obtain a crosslink density required for reducing the connection resistance.
[0029] From the viewpoint of reducing stickiness of the composition, the content of the (B1) component in the adhesive composition may be 60 to 95 mass %, 65 to 90 mass %, or 70 to 85 mass %, based on the total mass of the (B) component.
[0030] Furthermore, from the viewpoint of making it easier to obtain the crosslink density required to reduce the connection resistance, the content of the (B1) component in the adhesive composition may be 10 to 70 mass %, 20 to 60 mass %, or 30 to 50 mass % based on the total mass of the resin components of the adhesive composition (e.g., components other than the conductive particles and the filler).
[0031] The component (B2) may be a (poly)urethane (meth)acrylate compound having an allophanate bond (-NH-CO-N-COO- group) in the molecule. In this case, it is easy to achieve both an improvement in temporary fixing strength and a reduction in connection resistance.
[0032] The component (B2) may be trifunctional or tetrafunctional.
[0033] From the viewpoint of improving temporary fixing strength, the content of the (B2) component in the adhesive composition may be 2 to 50 mass %, 5 to 40 mass %, or 10 to 30 mass %, based on the total mass of the (B) component.
[0034] From the viewpoint of improving temporary fixing strength, the content of the component (B2) in the adhesive composition may be 2 to 40 mass %, 2 to 30 mass %, or 5 to 20 mass %, based on the total mass of the resin components of the adhesive composition (e.g., components other than the conductive particles and the filler).
[0035] Furthermore, from the viewpoint of improving temporary fixing strength, the content of the (B2) component in the adhesive composition may be 2 to 50 parts by mass, 5 to 40 parts by mass, or 10 to 30 parts by mass, relative to 100 parts by mass of the total content of the (B1) component and the (B2) component.
[0036] The adhesive composition of the present embodiment may further contain, as component (B), a radically polymerizable compound other than components (B1) and (B2) (hereinafter also referred to as “component (B3)”).
[0037] Examples of the component (B3) include a (meth)acrylate compound, a maleimide compound, a vinyl ether compound, an allyl compound, a styrene derivative, and a nadimide derivative.
[0038] Examples of the (meth)acrylate compound include epoxy (meth)acrylate, (poly)urethane (meth)acrylate other than the components (B1) and (B2), methyl (meth)acrylate, polyether (meth)acrylate, polyester (meth)acrylate, polybutadiene (meth)acrylate, silicone acrylate, ethyl (meth)acrylate, 2-cyanoethyl (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. , n-hexyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, isopropyl (meth)acrylate, hydroxypropyl (meth)acrylate, isobutyl (meth)acrylate, isobornyl (meth)acrylate, isodecyl (meth)acrylate, isooctyl (meth)acrylate, n-lauryl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, 2-(meth)acryloyloxyethyl phosphate acrylate, N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, polyethylene glycol di(meth)acrylate, polyalkylene glycol di(meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate , neopentyl glycol di(meth)acrylate, pentaerythritol (meth)acrylate, dipentaerythritol hexa(meth)acrylate, isocyanuric acid modified bifunctional (meth)acrylate, isocyanuric acid modified trifunctional (meth)acrylate, tricyclodecanyl acrylate, dimethylol-tricyclodecane diacrylate, 2-hydroxy-1,3-diacryloxypropane, 2,2-bis[4-(acryloxymethoxy)phenyl]propane, 2,2-bis[4-(acryloxypolyethoxy)phenyl]propane, 2,Examples include 2-di(meth)acryloyloxydiethyl phosphate and 2-(meth)acryloyloxyethyl acid phosphate.
[0039] Examples of the maleimide compound include 1-methyl-2,4-bismaleimidebenzene, N,N'-m-phenylene bismaleimide, N,N'-p-phenylene bismaleimide, N,N'-m-toluylene bismaleimide, N,N'-4,4-biphenylene bismaleimide, N,N'-4,4-(3,3'-dimethyl-biphenylene) bismaleimide, N,N'-4,4-(3,3'-dimethyldiphenylmethane) bismaleimide, N,N'-4,4-(3,3'-diethyldiphenylmethane) bismaleimide, N,N'-4,4-diphenylmethane bismaleimide, and N,N'-4,4-diphenylpropane. Examples of such maleimide include pan bismaleimide, N,N'-4,4-diphenyl ether bismaleimide, N,N'-3,3-diphenyl sulfone bismaleimide, 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane, 2,2-bis(3-s-butyl-4-8(4-maleimidophenoxy)phenyl)propane, 1,1-bis(4-(4-maleimidophenoxy)phenyl)decane, 4,4'-cyclohexylidene-bis(1-(4maleimidophenoxy)-2-cyclohexyl)benzene, and 2,2'-bis(4-(4-maleimidophenoxy)phenyl)hexafluoropropane.
[0040] Examples of the vinyl ether compound include diethylene glycol divinyl ether, dipropylene glycol divinyl ether, cyclohexane dimethanol divinyl ether, and trimethylolpropane trivinyl ether.
[0041] Examples of the allyl compound include 1,3-diallyl phthalate, 1,2-diallyl phthalate, and triallyl isocyanurate.
[0042] The component (B3) may be a (meth)acrylate compound from the viewpoint of achieving a good balance between the curing reaction rate and the physical properties after curing. The component (B3) may be a (meth)acrylate compound having a high Tg skeleton such as a dicyclopentadiene skeleton from the viewpoint of improving the cohesive force and further reducing the connection resistance.
[0043] From the viewpoint of improving adhesive strength, the component (B3) may contain a (meth)acrylate compound represented by the following formula (BP) (a (meth)acrylate compound having a phosphoric acid ester structure). [ka] In formula (BP), n represents an integer of 1 to 3, and R represents a hydrogen atom or a methyl group.
[0044] The (meth)acrylate compound represented by formula (BP) can be obtained, for example, by reacting phosphoric anhydride with 2-hydroxyethyl (meth)acrylate. Specific examples of the (meth)acrylate compound represented by formula (1) include mono(2-(meth)acryloyloxyethyl)acid phosphate, di(2-(meth)acryloyloxyethyl)acid phosphate, etc.
[0045] The content of the (meth)acrylate compound represented by formula (BP) may be, for example, 1 to 10 mass %, 2 to 5 mass %, or 2.5 to 4 mass % based on the total mass of the component (B), in that it is easier to obtain a crosslink density required for reducing connection resistance and improving connection reliability.
[0046] The content of component (B) in the adhesive film for circuit connection may be 20 to 80 mass %, 30 to 70 mass %, or 40 to 65 mass % based on the total mass of the resin components of the adhesive composition (e.g., components other than the conductive particles and filler), in terms of reducing connection resistance and making it easier to obtain the crosslink density required to improve high-temperature and high-humidity resistant connection reliability.
[0047] [Component (C): Radical polymerization initiator] Examples of the component (C) include initiators that generate free radicals by heat (heating), initiators that generate free radicals by light, and initiators that generate free radicals by ultrasonic waves, electromagnetic waves, etc. From the viewpoint of achieving better connection reliability, the component (C) may be a thermal radical polymerization initiator.
[0048] The initiator that generates free radicals by heat decomposes by heat to generate free radicals. That is, the thermal radical polymerization initiator is a compound that generates radicals by applying thermal energy from the outside. Examples of the thermal radical polymerization initiator include organic peroxides and azo compounds that have been known in the past. Such radical polymerization initiators are appropriately selected depending on the intended connection temperature, connection time, pot life, and the like. From the viewpoints of stability, reactivity, and compatibility, the initiator may be an organic peroxide having a one-minute half-life temperature of 90 to 175°C and a weight average molecular weight of 180 to 1000. By having the one-minute half-life temperature in this range, the storage stability is further excellent, the radical polymerizability is sufficiently high, and the initiator can be cured in a short time.
[0049] Specific examples of initiators that generate free radicals by heat include diacyl peroxides, peroxydicarbonates, peroxy esters, peroxy ketals, dialkyl peroxides, hydroperoxides, and silyl peroxides.
[0050] As the radical polymerization initiator, from the viewpoint of suppressing corrosion of electrodes (circuit electrodes, etc.), an initiator containing chlorine ions and organic acids at a concentration of 5000 ppm or less is preferable, and an initiator that generates less organic acid after thermal decomposition is more preferable. Specific examples of such initiators include peroxyesters, dialkyl peroxides, hydroperoxides, and silyl peroxides. Among these, peroxyesters may be used from the viewpoint of obtaining high reactivity.
[0051] Specific examples of component (C) include 1,1,3,3-tetramethylbutyl peroxyneodecanoate, di(4-t-butylcyclohexyl) peroxydicarbonate, di(2-ethylhexyl) peroxydicarbonate, cumyl peroxyneodecanoate, dilauroyl peroxide, 1-cyclohexyl-1-methylethyl peroxyneodecanoate, t-hexyl peroxyneodecanoate, t-butyl peroxyneodecanoate, and t-butyl peroxypi. Valate, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, 2,5-dimethyl-2,5-di(2-ethylhexanoylperoxy)hexane, t-hexylperoxy-2-ethylhexanoate, t-butylperoxy-2-ethylhexanoate, t-butylperoxyneoheptanoate, t-amylperoxy-2-ethylhexanoate, di-t-butylperoxyhexahydroterephthalate, t-amylperoxy-3,5,5 -Trimethylhexanoate, 3-hydroxy-1,1-dimethylbutyl peroxyneodecanoate, t-amyl peroxyneodecanoate, di(3-methylbenzoyl) peroxide, dibenzoyl peroxide, di(4-methylbenzoyl) peroxide, t-hexylperoxyisopropyl monocarbonate, t-butylperoxymaleate, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxylaurate, 2,5 -Dimethyl-2,5-di(3-methylbenzoylperoxy)hexane, t-butylperoxy-2-ethylhexyl monocarbonate, t-hexyl peroxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-butyl peroxybenzoate, dibutyl peroxytrimethyladipate, t-amyl peroxy normal octoate, t-amyl peroxy isononanoate, t-amyl peroxybenzoate, and other organic peroxides;Examples of azo compounds include 2,2'-azobis-2,4-dimethylvaleronitrile, 1,1'-azobis(1-acetoxy-1-phenylethane), 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 4,4'-azobis(4-cyanovaleric acid), and 1,1'-azobis(1-cyclohexanecarbonitrile).
[0052] The content of the (C) component may be 0.1% by mass or more, 0.5% by mass or more, or 1% by mass or more based on the total mass of the resin components of the adhesive composition (e.g., components other than the conductive particles and filler). From the viewpoint of pot life, the content of the (C) component may be 30% by mass or less, 20% by mass or less, or 10% by mass or less based on the total mass of the adhesive components of the adhesive composition (e.g., components other than the conductive particles and filler). From these viewpoints, the content of the (C) component may be 0.1 to 30% by mass, 0.5 to 20% by mass, or 1 to 10% by mass based on the total mass of the adhesive components of the adhesive composition (e.g., components other than the conductive particles and filler).
[0053] The adhesive composition may further contain other components in addition to the components (A), (B), and (C), such as conductive particles, coupling agents, fillers, softeners, accelerators, deterioration inhibitors, colorants, flame retardants, and thixotropic agents.
[0054] The conductive particles are not particularly limited as long as they are conductive particles, and may be metal particles made of metals such as Au, Ag, Ni, Cu, solder, etc., or conductive carbon particles made of conductive carbon. The conductive particles may be coated conductive particles having a core containing non-conductive glass, ceramic, plastic (polystyrene, etc.), etc., and a coating layer containing the above metal or conductive carbon and coating the core. Among these, metal particles formed of a heat-fusible metal, or coated conductive particles having a core containing plastic and a coating layer containing a metal or conductive carbon and coating the core are preferably used. In this case, since it is easy to deform the cured product of the adhesive composition by heating or pressure, when the electrodes are electrically connected to each other, the contact area between the electrodes and the conductive particles can be increased, and the conductivity between the electrodes can be further improved.
[0055] The conductive particles may be insulating coated conductive particles comprising the above-mentioned metal particles, conductive carbon particles or coated conductive particles, and an insulating layer containing an insulating material such as resin and coating the surface of the particles. When the conductive particles are insulating coated conductive particles, even if the content of the conductive particles is high, the surface of the particles is coated with resin, so that the occurrence of short circuits due to contact between the conductive particles can be suppressed, and the insulation between adjacent electrode circuits can be improved. The conductive particles may be one type of the above-mentioned various conductive particles alone or two or more types in combination.
[0056] The maximum particle size of the conductive particles must be smaller than the minimum interval between the electrodes (the shortest distance between adjacent electrodes). From the viewpoint of excellent dispersibility and conductivity, the maximum particle size of the conductive particles may be 1.0 μm or more, 2.0 μm or more, or 2.5 μm or more. From the viewpoint of excellent dispersibility and conductivity, the maximum particle size of the conductive particles may be 50 μm or less, 30 μm or less, or 20 μm or less. From these viewpoints, the maximum particle size of the conductive particles may be 1.0 to 50 μm, 2.0 to 30 μm, or 2.5 to 20 μm. In this specification, the particle size of 300 arbitrary conductive particles (pcs) is measured by observation using a scanning electron microscope (SEM), and the largest value obtained is defined as the maximum particle size of the conductive particles. In addition, when the conductive particles are not spherical, such as having protrusions, the particle size of the conductive particles is defined as the diameter of a circle circumscribing the conductive particles in an SEM image.
[0057] The average particle size of the conductive particles may be 1.0 μm or more, 2.0 μm or more, or 2.5 μm or more, from the viewpoint of excellent dispersibility and conductivity. The average particle size of the conductive particle component may be 50 μm or less, 30 μm or less, or 20 μm or less, from the viewpoint of excellent dispersibility and conductivity. From these viewpoints, the average particle size of the conductive particles may be 1.0 to 50 μm, 2.0 to 30 μm, or 2.5 to 20 μm.
[0058] From the viewpoint of easily obtaining a stable connection resistance, the content of the conductive particles may be 0.5 to 50 mass %, 1 to 40 mass %, or 2 to 30 mass % based on the total amount of the adhesive composition.
[0059] Examples of the coupling agent include silane coupling agents having an organic functional group such as a (meth)acryloyl group, a mercapto group, an amino group, an imidazole group, an epoxy group, etc., silane compounds such as tetraalkoxysilane, tetraalkoxytitanate derivatives, polydialkyltitanate derivatives, etc. When a coupling agent is contained, the adhesiveness can be further improved.
[0060] The content of the coupling agent may be, for example, 0.1 mass % or more, 20 mass % or less, or may be 0.1 to 20 mass %, based on the total mass of the resin components in the adhesive composition.
[0061] Examples of the filler include non-conductive fillers (e.g., non-conductive particles). When the filler is contained, further improvement in connection reliability can be expected. The filler may be either an inorganic filler or an organic filler. Examples of the inorganic filler include inorganic fine particles such as metal oxide fine particles such as silica fine particles, alumina fine particles, silica-alumina fine particles, titania fine particles, and zirconia fine particles; and nitride fine particles. Examples of the organic filler include organic fine particles such as silicone fine particles, methacrylate-butadiene-styrene fine particles, acrylic-silicone fine particles, polyamide fine particles, and polyimide fine particles. These fine particles may have a uniform structure or a core-shell structure.
[0062] The content of the filler may be, for example, 1 vol % or more, 30 vol % or less, or 1 to 30 vol %, based on the total volume of the adhesive composition.
[0063] The accelerator may be a thiol compound. The thiol compound may be a thiol compound having one thiol group (monofunctional thiol compound), or may be a thiol compound having multiple thiol groups (multifunctional thiol compound). The thiol group may be a primary thiol group, a secondary thiol group, or a tertiary thiol group.
[0064] Examples of monofunctional thiol compounds include 2-mercaptobenzothiazole, 2-methyl-4,5-dihydrofuran-3-thiol, 3-mercapto-1-hexanol, mercaptomethylbutanol, 3-mercapto-2-methylpentanol, 3-mercapto-3-methylbutanol, 4-ethoxy-2-methyl-2-butanethiol, hexanethiol, isobutylthiol, 1,1-dimethylheptanethiol, 2-ethylhexyl-3-mercaptopropionate, n-octyl-3-mercaptopropionate, methoxybutyl-3-mercaptopropionate, and stearyl-3-mercaptopropionate.
[0065] Examples of polyfunctional thiol compounds include pentaerythritol tetrakis(3-mercaptobutyrate), ethanedithiol, 1,3-propanethiol, 1,4-butanethiol, trimethylolpropane tris(3-mercaptopropionate), tris-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, and tetraethylene glycol bis(3-mercaptopropionate).
[0066] The content of the accelerator may be, for example, 0.1 to 5 mass, 0.5 to 4 mass, or 0.5 to 2 mass, based on the total mass of the resin components of the adhesive composition (e.g., components other than the conductive particles and filler).
[0067] <Adhesive film for circuit connection> The adhesive film for circuit connection of this embodiment contains (A) a thermoplastic resin, (B) a radical polymerizable compound, and (C) a radical polymerization initiator, and can have a configuration similar to that of the adhesive composition of this embodiment described above.
[0068] With regard to the content of each component, "based on the total amount of the adhesive composition" shall be read as "based on the total amount of the adhesive film," and "based on the total mass of the resin components of the adhesive composition (e.g., components other than conductive particles and fillers)" shall be read as "based on the total mass of the resin components of the adhesive film (e.g., components other than conductive particles and fillers)."
[0069] When the adhesive film for circuit connection of this embodiment contains conductive particles, the particle density of the conductive particles in the adhesive film is set to 100 particles / mm from the viewpoint of obtaining a stable connection resistance. 2 More than 1000 pieces / mm 2 or more than 3000 pieces / mm 2 From the viewpoint of ensuring the insulation between adjacent electrodes, the particle density of the conductive particles in the adhesive film may be 100,000 particles / mm 2 Below, 50000 pieces / mm 2 or less than 30,000 pieces / mm 2 From these viewpoints, the particle density of the conductive particles in the adhesive film may be 100 to 100,000 particles / mm 2 , 1000~50000 pieces / mm 2 , or 3000 to 30000 pieces / mm 2 It may be.
[0070] The thickness of the adhesive film for circuit connection may be appropriately set depending on the height of the electrodes of the circuit members to be bonded, etc. From the viewpoint of being able to sufficiently fill the space between the electrodes to seal the electrodes and obtain better connection reliability, the thickness may be 5 μm or more, may be 200 μm or less, or may be 5 to 200 μm.
[0071] The adhesive film for circuit connection of this embodiment can be suitably used as an adhesive film for circuit connection for connecting a first circuit member having a first electrode (e.g., a first circuit member having a first circuit electrode formed on the main surface of a first substrate) and a second circuit member having a second electrode (e.g., a second circuit member having a second circuit electrode formed on the main surface of a second substrate) with the first electrode and the first electrode (the first circuit electrode and the second circuit electrode) arranged opposite each other.
[0072] When the adhesive film for circuit connection contains conductive particles, it can function as an anisotropic conductive adhesive film having anisotropic conductivity.
[0073] The circuit connecting adhesive film may be an adhesive film for circuit connecting that does not contain conductive particles.
[0074] The circuit connection adhesive film of this embodiment can be produced by the following method. Specifically, first, the components (A), (B), and (C), as well as other components added as necessary, are added to a solvent (organic solvent), and dissolved or dispersed by stirring, mixing, kneading, etc. to prepare a varnish composition (varnish-like adhesive composition). Thereafter, the varnish composition is applied to a release-treated substrate using a knife coater, roll coater, applicator, comma coater, die coater, etc., and the solvent is volatilized by heating to form a circuit connection adhesive film on the substrate.
[0075] The solvent used in preparing the varnish composition may be a solvent that has the property of dissolving or dispersing each component uniformly. Examples of such solvents include toluene, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, propyl acetate, and butyl acetate. These solvents can be used alone or in combination of two or more. The stirring and mixing and kneading in preparing the varnish composition can be performed using, for example, a stirrer, a grinding machine, a three-roll mill, a ball mill, a bead mill, or a homodisper.
[0076] The substrate is not particularly limited as long as it has heat resistance sufficient to withstand the heating conditions for volatilizing the solvent. For example, substrates (e.g., films) made of oriented polypropylene (OPP), polyethylene terephthalate (PET), polyethylene naphthalate, polyethylene isophthalate, polybutylene terephthalate, polyolefin, polyacetate, polycarbonate, polyphenylene sulfide, polyamide, polyimide, cellulose, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinylidene chloride, synthetic rubber, liquid crystal polymer, etc. can be used.
[0077] The heating conditions for volatilizing the solvent from the varnish composition applied to the substrate may be conditions that allow the solvent to volatilize sufficiently, for example, at 40° C. or higher and 120° C. or lower for 0.1 minutes or longer and 10 minutes or shorter.
[0078] In the adhesive film for circuit connection of this embodiment, a part of the solvent may remain unremoved. The content of the solvent in the adhesive film for circuit connection of this embodiment may be, for example, 10 mass % or less, or 5 mass % or less, based on the total mass of the adhesive film.
[0079] <Circuit connection structure and method for producing same> Next, the circuit connection structure and the method for producing the same will be described.
[0080] The circuit connection structure of the present embodiment comprises a first circuit member having a first electrode, a second circuit member having a second electrode, and a connection portion disposed between the first circuit member and the second circuit member and electrically connecting the first electrode and the second electrode to each other, the connection portion comprising the adhesive composition of the present embodiment or a cured product of the adhesive film for circuit connection of the present embodiment.
[0081] The method for producing the circuit connection structure of the present embodiment includes a step of thermocompression bonding a first circuit member having a first electrode and a second circuit member having a second electrode with the circuit connection adhesive film of the present embodiment interposed between the first circuit member and the second circuit member, thereby electrically connecting the first electrode and the second electrode to each other.
[0082] 1 is a schematic cross-sectional view showing one embodiment of a circuit connection structure. As shown in the figure, the circuit connection structure 1 includes a first circuit member 4 having a first electrode 42, a second circuit member 5 having a second electrode 52, and a connection portion 6 disposed between the first circuit member 4 and the second circuit member 5, electrically connecting the first electrode 42 and the second electrode 52 to each other. The first circuit member 4 and the second circuit member 5 are disposed such that the first electrode 42 and the second electrode 52 face each other.
[0083] The first circuit member 4 includes, for example, a first substrate 41 (e.g., a circuit substrate) and a first electrode 42 (e.g., a circuit electrode) formed on a main surface 41a of the first substrate 41. Note that an insulating layer (not shown) may be formed on the main surface 41a of the first substrate 41, if necessary.
[0084] The second circuit member 5 includes, for example, a second substrate 51 (e.g., a circuit substrate) and a second electrode 52 (e.g., a bump electrode) formed on a main surface 51a of the second substrate 51. Also, on the main surface 51a of the second substrate 51, an insulating layer (not shown) may be formed in some cases.
[0085] There is no particular limitation on the first circuit member 4 and the second circuit member 5, so long as they are members on which electrodes that require electrical connection are formed. As the first substrate and the second substrate, inorganic substrates such as semiconductors, glass, ceramics, etc.; polyimide substrates such as TCP, FPC, COF, etc.; substrates on which electrodes are formed on films such as polycarbonate, polyester, polyethersulfone, etc.; printed wiring boards, etc., may be used, and a combination of two or more of these may also be used.
[0086] The first electrode and the second electrode may be formed of gold, silver, tin, ruthenium, rhodium, palladium, osmium, iridium, platinum, copper, aluminum, molybdenum, titanium, indium tin oxide (ITO), indium zinc oxide (IZO), indium gallium zinc oxide (IGZO), etc. The first electrode and the second electrode may be circuit electrodes or bump electrodes. At least one of the first electrode and the second electrode may be a bump electrode.
[0087] The first circuit member and the second circuit member may be the same or different from each other. The first circuit member and the second circuit member may be a glass substrate or a plastic substrate on which the above-mentioned electrodes are formed, a printed wiring board, a ceramic wiring board, a flexible wiring board, a semiconductor silicon IC chip, or the like.
[0088] The connection portion 6 is a portion formed by curing the adhesive film for circuit connection 11, and contains the cured product of the adhesive film for circuit connection 11. As shown in Fig. 1, the connection portion 6 contains, for example, conductive particles P and an insulating material 7 formed by curing components (such as adhesive components) other than the conductive particles in the adhesive film for circuit connection 11. The connection portion 6 spreads in a layer shape along the main surface 41a of the first circuit member 4 and the main surface 51a of the second circuit member 5.
[0089] The conductive particles P are disposed between the first electrode 42 and the second electrode 52. The conductive particles P are in contact with the first electrode 42 and the second electrode 52 in a state where they are slightly deformed into a flat shape by compression. This realizes an electrical connection between the first electrode 42 and the second electrode 52. The conductive particles P may be disposed not only between the opposing first electrode 42 and second electrode 52, but also between the main surface 41a of the first substrate 41 and the main surface 51a of the second substrate 51.
[0090] <Method of Manufacturing Connection Structure> A method for producing the connection structure 1 includes, for example, a step of thermocompression bonding the first member 4 and the second member 5 with an adhesive film for circuit connection 11 interposed between the first member 4 and the second member 5, thereby electrically connecting the first electrode 42 and the second electrode 52 to each other. Hereinafter, the method for producing the connection structure 1 will be described with reference to FIG. 2.
[0091] 2 is a schematic cross-sectional view showing a manufacturing process for the connection structure 1. In the example shown in the figure, first, a first circuit member 4 and an adhesive film for circuit connection 11 are prepared (see FIG. 2(a)).
[0092] Next, the adhesive film for circuit connection 11 is placed on the main surface 41a of the first circuit member 4. When using a laminate in which the adhesive film for circuit connection 11 is laminated on a support, the laminate is placed on the first circuit member 4 with the adhesive film for circuit connection 11 side facing the first circuit member 4.
[0093] Next, the adhesive film for circuit connection 11 is pressed in the directions of arrows A and B in Fig. 2(a) to temporarily connect the adhesive film for circuit connection 11 to the first circuit member 4 (see Fig. 2(b)). At this time, heating may be performed together with the pressing.
[0094] 2(c), a second circuit member 5 is further placed on the adhesive film 11 for circuit connection placed on the first circuit member 4, with the second electrode 52 facing the first circuit member 4 (i.e., with the first electrode 42 and the second electrode 52 placed opposite each other). If the adhesive film 11 for circuit connection is laminated on a support (not shown), the support is peeled off and then the second circuit member 5 is placed on the adhesive film 11 for circuit connection.
[0095] At this time, the first electrode 42 and the second electrode 52 are aligned so as to face each other, and then the second circuit member 30 is heated and pressurized to be temporarily fixed. This makes it possible to prevent problems such as the circuit member being displaced or dropped during transportation. It also makes it possible to suppress the electrodes from being displaced during the subsequent full connection. The heating temperature during temporary fixing is set to a temperature lower than the temperature at which the circuit connecting material 5 in the film-like adhesive 40 does not harden, and the time from alignment to completion of temporary fixing may be 5 seconds or less in order to reduce throughput.
[0096] Then, while being heated, the adhesive film for circuit connection 11 is pressed in the directions of arrows A and B in Fig. 2(c). This causes the adhesive film for circuit connection 11 to harden and complete the connection. As a result, a connection structure 1 as shown in Fig. 1 is obtained.
[0097] The heating temperature of the adhesive film for circuit connection 11 is preferably equal to or higher than the temperature at which active polymerization species are generated in the curing agent and polymerization of the monomer (polymerizable compound) is initiated. The heating temperature may be, for example, 80° C. to 200° C., 100° C. to 180° C., or 90° C. to 170° C. The heating time may be, for example, 0.1 seconds to 30 seconds, 1 second to 20 seconds, 10 seconds or less, or 5 seconds or less. EXAMPLES
[0098] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0099] <Synthesis of polyurethane acrylate (UA1)> Into a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser having a calcium chloride drying tube, and a nitrogen gas inlet tube, 2500 parts by mass (2.50 mol) of poly(1,6-hexanediol carbonate) (trade name: Duranol T5652, manufactured by Asahi Kasei Chemicals Corporation, number average molecular weight 1000) and 666 parts by mass (3.00 mol) of isophorone diisocyanate (manufactured by Sigma-Aldrich Co.) were uniformly dropped over 3 hours. Next, after sufficient nitrogen gas was introduced into the reaction vessel, the inside of the reaction vessel was heated to 70 to 75°C to cause a reaction. Next, 0.53 parts by mass (4.3 mmol) of hydroquinone monomethyl ether (Sigma-Aldrich) and 5.53 parts by mass (8.8 mmol) of dibutyltin dilaurate (Sigma-Aldrich) were added to the reaction vessel, and then 238 parts by mass (2.05 mol) of 2-hydroxyethyl acrylate (Sigma-Aldrich) were added and reacted at 70°C for 6 hours under air atmosphere. This resulted in polyurethane acrylate (UA1). The weight-average molecular weight of polyurethane acrylate (UA1) was 15,000. The weight-average molecular weight was measured by gel permeation chromatography (GPC) using a calibration curve based on standard polystyrene under the following conditions. (Measurement conditions) Equipment: Tosoh Corporation GPC-8020 Detector: Tosoh RI-8020 Column: Gelpack GLA160S+GLA150S manufactured by Hitachi Chemical Co., Ltd. Sample concentration: 120mg / 3mL Solvent: Tetrahydrofuran Injection volume: 60μL Pressure: 2.94×10 6 Pa(30kgf / cm 2 ) Flow rate: 1.00mL / min
[0100] <Preparation of conductive particles> A layer of nickel was formed on the surface of polystyrene particles to a thickness of 0.2 μm, thereby obtaining conductive particles with an average particle size of 4 μm, a maximum particle size of 4.5 μm, and a specific gravity of 2.5.
[0101] (Examples 1 to 4, Comparative Examples 1 to 4) [Preparation of adhesive film] The components shown below were mixed in the amounts (parts by mass) shown in Table 1 to prepare respective varnish compositions.
[0102] (thermoplastic resin) A1: Bisphenol A phenoxy resin (product name: PKHC, manufactured by Union Carbide)
[0103] (Radical polymerizable compound) B1: Polyurethane acrylate (UA1) synthesized as described above B2-1: 4-functional aliphatic urethane acrylate (product name: EBECRYL 4666, manufactured by Daicel-Allnex) B2-2: Trifunctional aliphatic urethane acrylate (product name: EBECRYL 4740, manufactured by Daicel Allnex Co., Ltd.) B3-1: Isocyanuric acid EO modified diacrylate (product name: M-215, manufactured by Toagosei Co., Ltd.) B3-2: 2-Methacryloyloxyethyl acid phosphate (product name: Light Ester P-2M, manufactured by Kyoeisha Chemical Co., Ltd.) (Radical polymerization initiator) C1: Benzoyl peroxide (product name: Niper BMT-K40, manufactured by NOF Corporation) (Conductive particles) D1: Conductive particles prepared as described above (Coupling Agent) E1: 3-methacryloxypropyltrimethoxysilane (product name: KBM503, manufactured by Shin-Etsu Chemical Co., Ltd.) (Accelerator) F1: Pentaerythritol tetrakis(3-mercaptobutyrate) (product name: Karenz MT PE-1 ("Karenz MT" is a registered trademark), manufactured by Showa Denko K.K.) (filling material) G1: Silica fine particles (product name: R104, manufactured by Nippon Aerosil Co., Ltd., average particle size (primary particle size): 12 nm) (solvent) H1: Methyl ethyl ketone
[0104] The varnish composition obtained above was applied onto a PET film having a thickness of 50 μm using a coating device, and then hot air dried at 70° C. for 3 minutes to form an adhesive film for circuit connection having a thickness (thickness after drying) of 22 μm on the PET film.
[0105] [Preparation of samples for measuring temporary fixing force] A 25μm pitch COF (manufactured by FLEXSEED) and a SiNx substrate (thickness 0.7mm) with a 0.2μm thick silicon nitride (SiNx) thin layer on a glass substrate were temporarily fixed via the prepared circuit connection adhesive film to obtain a sample for measuring temporary fixing force. Temporary fixing was performed using an alignment device (manufactured by Ohashi Manufacturing Co., Ltd.) by heating and pressing at 90℃, 1MPa, for 2 seconds, over a width of 1.2mm and length of 4cm.
[0106] [Evaluation of the sample for measuring temporary fixing force] The obtained samples for measuring temporary fixing strength were evaluated as follows.
[0107] (Temporary fixing force) The adhesive strength of the obtained temporary fixing force measurement sample was measured by a 90-degree peel method in accordance with JIS-Z 0237. Note that, as an adhesive strength measurement device, Tensilon UTM-4 (product name, manufactured by Toyo Baldwin Co., Ltd., peel strength 50 mm / min, 25°C) was used.
[0108] [Fabrication of circuit connection structure] A flexible circuit board (FPC) with a pitch of 200 μm and a glass substrate with thin-film electrodes made of IZO on the glass substrate were connected via the prepared circuit connection adhesive film over a width of 1.2 mm by heating and pressurizing at 170°C, 4 MPa for 7 seconds using a thermocompression bonding device (heating method: constant heat type, manufactured by Taiyo Kikai Seisakusho Co., Ltd.), to produce a circuit connection structure (connection structure).
[0109] [Evaluation of circuit connection structures] The resulting circuit connection structure was evaluated as follows.
[0110] (Connection resistance) The connection resistance between the opposing electrodes of the resulting circuit connection structure immediately after connection was measured with a multimeter, and was calculated as the average value of the resistance between the opposing electrodes at 24 points.
[0111] [Preparation of samples for measuring glass adhesion] The prepared circuit connection adhesive film was attached to a 2.5 mm wide area on a SiNx substrate (0.7 mm thick) with a 0.2 μm thick silicon nitride (SiNx) thin layer on a glass substrate by applying heat and pressure at 70°C, 1 MPa, and 1 second using a thermocompression device. Then, a 2.3 mm wide tape was fixed to the attached adhesive film.
[0112] [Evaluation of glass adhesion measurement samples] The obtained glass adhesion measurement samples were subjected to the following evaluations.
[0113] (glass adhesion) The adhesion strength of the obtained glass adhesion measurement sample was measured by a 90-degree peel method in accordance with JIS-Z 0237. A Tensilon UTM-4 (trade name, manufactured by Toyo Baldwin Co., Ltd., peel strength 50 mm / min, 25° C.) was used as an adhesion strength measurement device.
[0114] [Table 1]
[0115] As shown in Table 1, the adhesive films for circuit connection of Examples 1 to 4 can temporarily fix components together with a high temporary fixing force, and can obtain a connection structure with a sufficiently low connection resistance even under connection conditions of 170°C, 4 MPa, and 7 seconds. Furthermore, the adhesive films for circuit connection of Examples 1 to 4 can exhibit excellent temporary fixing force while also maintaining sufficient adhesion to glass. [Explanation of symbols]
[0116] 1...connection structure, 4...first circuit member, 5...second circuit member, 6...connection portion, 42...first electrode, 52...second electrode, 11...circuit connection adhesive film, P...conductive particles.
Claims
1. A thermoplastic resin, a radical polymerizable compound, and a radical polymerization initiator, The adhesive composition contains, as the radical polymerizable compounds, a first (poly)urethane (meth)acrylate compound having a weight average molecular weight of 10,000 to 55,000, and a second (poly)urethane (meth)acrylate compound having a weight average molecular weight of 500 to 1,500.
2. The adhesive composition according to claim 1 , wherein the second (poly)urethane (meth)acrylate compound has an allophanate bond in the molecule.
3. The adhesive composition according to claim 1, wherein the content of the second (poly)urethane (meth)acrylate compound is 5 to 35 parts by mass per 100 parts by mass of the first (poly)urethane (meth)acrylate compound.
4. A thermoplastic resin, a radical polymerizable compound, and a radical polymerization initiator, The adhesive film for circuit connection contains, as the radical polymerizable compounds, a first (poly)urethane (meth)acrylate compound having a weight average molecular weight of 10,000 to 55,000, and a second (poly)urethane (meth)acrylate compound having a weight average molecular weight of 500 to 1,500.
5. 5. The adhesive film for circuit connection according to claim 4, wherein the second (poly)urethane (meth)acrylate compound has an allophanate bond in the molecule.
6. The adhesive film for circuit connection according to claim 4, wherein the content of the second (poly)urethane (meth)acrylate compound is 5 to 35 parts by mass per 100 parts by mass of the first (poly)urethane (meth)acrylate compound.
7. a first circuit member having a first electrode, a second circuit member having a second electrode, and a connection portion disposed between the first circuit member and the second circuit member, electrically connecting the first electrode and the second electrode to each other; A circuit connection structure, wherein the connection portion comprises a cured product of the adhesive composition according to any one of claims 1 to 3.
8. A method for producing a circuit connection structure, comprising a step of thermocompression bonding a first circuit member having a first electrode and a second circuit member having a second electrode, with the adhesive film for circuit connection according to any one of claims 4 to 6 interposed between the first circuit member and the second circuit member, to electrically connect the first electrode and the second electrode to each other.
Citation Information
Patent Citations
Anisotropically conductive adhesive and anisotropically conductive adhesive film
JP2006022231A
Adhesive composition, circuit connecting structure, and semiconductor device
JP2009001765A
Circuit connecting material and structure for connecting circuit member
WO2009063827A1